CYTOLOGICAL COMPARISON BETWEEN TECHNIQUES AND CITOESCOBILLA AYRE SPATULA (CYTOBRUSH) IN THE SAMPLING CERVICOVAGINAL - Arias Stella, Javier (2015)
Objective: To compare Ayre spatula and cytobrush methods in uterine cervix premalignant and malignant lesions detection. Material and Methods: Endocervical smears taken from 140 patients with the Ayre spatula and cytobrush methods were extended on separate codified slides and examined by two different pathologists unaware of the smear collection method. Bethesda system was used for diagnosis. Results: Sixty-five versus thirty-five per cent of the samples had endocervical cells respectively obtained with the cytobrush and the Ayre spatula method. When analyzing the quantity of endocervical cells, the samples obtained with the cytobrush method had more than five clusters of endocervical cells (71,4%) than with the Ayre spatula method (36,4%). Conclusion: Cytobrush method seems to be more efficient than Ayre spatula method for obtaining endocervical cells.